2021
DOI: 10.1038/s41598-021-01610-x
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity dynamics in Irish mudflats between microorganisms including Vibrio spp., common cockles Cerastoderma edule, and shorebirds

Abstract: Shellfish, including the key species the common cockle Cerastoderma edule, living and feeding in waters contaminated by infectious agents can accumulate them within their tissues. It is unknown if microbial pathogens and microparasites can subsequently be transmitted via concomitant predation to their consumers, including shorebirds. The objective of this study was to assess if pathogens associated with C. edule could be detected seasonally in the faeces of shorebirds that feed on C. edule and in the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…One study examined the shared microbiota between wild Hooded Cranes (Grus monacha) and domestic geese ( Anser anser ) using Miseq – Grimontia hollisae was identified as a potential pathogen, but the total number of birds colonized was not reported [123]. A longitudinal microbiome study involving shorebirds off the coast of Cork, Ireland discovered Grimontia hollisae in fecal samples, however, the number of samples positive/examined was not enumerated [124]. Clinical signs or mortality were not reported from either study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study examined the shared microbiota between wild Hooded Cranes (Grus monacha) and domestic geese ( Anser anser ) using Miseq – Grimontia hollisae was identified as a potential pathogen, but the total number of birds colonized was not reported [123]. A longitudinal microbiome study involving shorebirds off the coast of Cork, Ireland discovered Grimontia hollisae in fecal samples, however, the number of samples positive/examined was not enumerated [124]. Clinical signs or mortality were not reported from either study.…”
Section: Resultsmentioning
confidence: 99%
“…No study that tested for this pathogen reported clinical signs or a mortality event. Grimontia hollisae was rarely detected in birds, as we found only two studies, resulting in three study records, that searched for the pathogen in avian hosts [123, 124]. One study examined the shared microbiota between wild Hooded Cranes (Grus monacha) and domestic geese ( Anser anser ) using Miseq – Grimontia hollisae was identified as a potential pathogen, but the total number of birds colonized was not reported [123].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the environment in which these birds and primates and non-primate mammals live. These birds are wading birds whose feeding environment relies heavily on silt, which contains some fecal matter and some infectious Eimeria coccidia, thus making them susceptible to disease transmission [30]. Of course, it may also be due to birds being more susceptible to Eimeria, as Eimeria coccidia causes the most severe damage to poultry (belonging to birds).…”
Section: Discussionmentioning
confidence: 99%
“…Alongside whole bacterial microbiome data, we focused on detecting Vibrio species in the samples. Bacteria in the genus Vibrio include pathogenic and non-pathogenic taxa associated with human and wildlife diseases, and previous studies suggest that birds ingest potentially pathogenic vibrios and may spread them long distances [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%